Respon Pertumbuhan Dan Produksi Tanaman Pakcoy (Brassica Rapa L) Terhadap Pemberian Pupuk Kandang Ayam Dan Kompos Daun Lamtoro - Sapiril Hudalil Mustaqim; Dermawan Hutagaol; Nurma Ani (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
Response of growth and production of pakcoy plants (brassica rapa l) to the application of chicken manure and lamtoro leaf compost. The aim of this study was to observe the growth and production response of the pakcoy plant due to the application of manure and the application of lantoro leaf compost. This research was conducted on Jalan Eka Rasmi Gg Eka Nusa 11 Medan Johor, North Sumatra Province. This research was conducted from April to. May 2022. This study used a factorial randomized block design with 2 treatment factors and 3 replications. The first factor was the application of chicken manure (A) consisting of 3 levels, namely A0 = no treatment, A1 = 1.25 kg plot -2, and A2 = 2.5 kg plot -2. The second factor was the application of lamtoro leaf compost (L) consisting of 4 levels namely, L0 = no treatment, L1 = 1.25 kg plot-2, L2 = 2.5 kg plot-2 and L3 = 3.75 kg plot-2 . The results showed that the application of chicken manure had a very significant effect on the parameters of plant height, number of leaves, leaf length, leaf width, plant weight per sample and plant weight per plot. The application of lamtoro leaf compost had a very significant effect on the parameters of plant height, number of leaves, leaf length, leaf width, plant weight per sample and plant weight per plot. The interaction treatment showed no significant effect on all observation parameters.